2016
DOI: 10.1016/j.cub.2015.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Monomorphic Maps and Dimorphic Responses in Rat Genital Cortex

Abstract: Mammalian external genitals show sexual dimorphism [1, 2] and can change size and shape upon sexual arousal. Genitals feature prominently in the oldest pieces of figural art [3] and phallic depictions of penises informed psychoanalytic thought about sexuality [4, 5]. Despite this longstanding interest, the neural representations of genitals are still poorly understood [6]. In somatosensory cortex specifically, many studies did not detect any cortical representation of genitals [7-9]. Studies in humans debate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 37 publications
9
48
2
Order By: Relevance
“…Growth of genital cortex during puberty has been reported in the rat (Lenschow et al, ). The area of penis and clitoris representation as defined by the layer 4 cytochrome ‐ oxidase activity showed morphological growth when comparing prepubertal to adult animals.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Growth of genital cortex during puberty has been reported in the rat (Lenschow et al, ). The area of penis and clitoris representation as defined by the layer 4 cytochrome ‐ oxidase activity showed morphological growth when comparing prepubertal to adult animals.…”
Section: Resultsmentioning
confidence: 93%
“…Lenschow et al () reported a cortical monomorphism of penis and clitoris representation in the rat. This result is surprising, given the marked sexual dimorphism of rat external genitals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, in postpartum rodents, the frequency and duration of tactile stimulation from suckling pups is dramatically increased as infants spend around 50% of their awake time nursing (Champagne et al, 2007; Grota and Ader, 1974). Stronger afferent inputs from the nipples, resulting from the continuous nursing, may induce activity-dependent plasticity in S1 neurons similarly to the expansion of the female genital cortex during puberty (Lenschow et al, 2017,2016). …”
Section: Plasticity In the Somatosensory Cortex During Motherhoodmentioning
confidence: 99%